UPAYA PENGENALAN DAN IMPLEMENTASI DASAR NILAI KEBUDILUHURAN MELALUI KEGIATAN LITERASI PADA ANAK SEKOLAH DASAR DI GUNUNG PICUNG BOGOR - Rahayu, Sri; Anggraeni, Desy (PORTAL RISET DAN INOVASI PENGABDIAN MASYARAKAT, 2024)
The Community Service with the theme of Introduction and Implementation of Basic Values of Humanitarianism through Literacy Activities for Elementary School Children was carried out for a period of two months, starting from February to March 2024, in Gunung Picung Village, Bogor Regency, West Java Province. The target of this activity is productive education-aged children as the future successors of Gunung Picung village. The method used in implementing this community service is Community Based Research, which is a design of activities carried out in the community environment and involves community members. The service team carries out their activities through the stages of preliminary analysis, implementation, and evaluation. The program activities conducted include introducing and providing examples of the implementation of basic values of humanitarianism such as honesty, responsibility, tolerance, cooperation, mutual assistance, love, creativity, and innovation through literacy activities for elementary school children. We hope that the program we have designed and implemented will be beneficial in helping to build good character and personality for the future successors of Gunung Picung-Bogor village.